Potency of Sunkist Orange (Citrus sinensisL. Osbeck) against Kidney Histology of White Wistar Rats Induced by Gentamicin - Masdalena Nasution; Chrismis Novalinda Ginting; Edy Fachrial; I Nyoman Ehrich Lister (Faculty of Pharmacy, Universitas Gadjah Mada, 2020)
About 1.7%-58% of all cases of acute kidney failure are caused by gentamicin nephrotoxicity and consequently increasing urea and creatinine levels in the blood which are indications of damage to function. Oranges contain secondary metabolites such as flavonoids, alkaloids, coumarin, limonoid, keratinoid and essential oil that have pharmacological activities such as antioxidants, anti-inflammatory, anti-cancer, and also nephroprotector. The purpose of this study is to evaluate the nephroprotective activity of Citrus sinensis peel ethanol extract (EEKJS) on rats induced by gentamicin. Rats were induced using gentamicin at a dose of 80 mg/kgBW intraperitoneally on the 7th day after induced at a dose of 50 mg/kgBW, 100 mg/kgBW, and 200 mg/kgBW for 7 days. The results obtained from the ethanol extract of Citrus sinensis peel gave nephroprotective with the lowest serum creatinine and urea levels at a dose of 200 mg/kgBW which was 0.4±0.02 mg/dl and 43.33 ± 2.51 mg/dl and difference significantly (p<0.05) with a positive control group which was only induced by gentamicin and histopathological results showed significant cell damage in the positive control group that was only induced by gentamicin, and in the 50 mg/kgBW dose group, 100 mg/kgBW, 200 mg/kgBW had cell repair after gentamicin induction. Citrus sinensis are highly recommended to be a food supplement for kidney protection.